Muḥammad Iqbāl and his position on women’s issues - Shamsud, Professor Dr Salahuddin Bin Mohd (IJRDO - Journal of Social Science and Humanities Research, 2021)
First, we highlighted the biography of Iqbāl the poet, his life, scientific and intellectual culture, thoughts and philosophy, and his scientific books and poetry, because he was one of those reformers who addressed the women’s issues. Second, we mentioned his position on the women’s issues in the East and the West that were selected from his books and poetry, because these issued were not mentioned in one particular book or a certain place, as they were spread in his multiple books and poems. Those women’s issues that were addressed by Iqbāl were as: Women’s Motherhood, Women’s Freedom, Women’s Marital Relationship and the Perfect woman in the opinion of Iqbāl. No doubt, the men and women are two pillars of human civilization. Each of them is a part cannot be separated from the history of human civilization and urbanization, women cannot be separated from a subject related to the human society and civilization. In fact they are two equal wheels of the cart of human life since the beginning of creation of the male and female, as she is equal to the man since ever, and the essential differences that separate them are those on which the Great Creative Creator, God almighty, and they still remain and will remain until the Day of Judgment. Iqbāl addresses Muslim women, explaining that Fatima Zahra is an ideal woman and good example, so all women must follow her virtuous qualities and avoid the cunning, deception, debauchery and corrupt upbringing that the times have brought.